2013
DOI: 10.1016/j.echo.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prediction Model to Estimate the Risk for Coarctation of the Aorta in the Presence of a Patent Ductus Arteriosus

Abstract: Objective To create a model to help identify coarctation of the aorta (CoA) in neonates with a patent ductus arteriosus (PDA). Background Diagnosing CoA in the presence of a PDA may require observation until PDA closure. We created a model incorporating previously published indices to estimate the probability of neonatal CoA in the presence of a PDA. Methods A retrospective “investigation” cohort of 80 neonates was divided into two groups: (1) neonates with PDA and suspicion for CoA requiring observation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The distance from the carotid artery to subclavian artery measured on neonatal echocardiogram has been shown to be useful in predicting CoA in the presence of a large DA. This is theorized to be secondary to a stretch or change in contour of the transverse to proximal DAo (including the isthmus) in patients with coarctation . Using the sagittal view of the fetal aortic arch, we found that similar contour changes exist in the fetus and could be employed for identification of CoA.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The distance from the carotid artery to subclavian artery measured on neonatal echocardiogram has been shown to be useful in predicting CoA in the presence of a large DA. This is theorized to be secondary to a stretch or change in contour of the transverse to proximal DAo (including the isthmus) in patients with coarctation . Using the sagittal view of the fetal aortic arch, we found that similar contour changes exist in the fetus and could be employed for identification of CoA.…”
Section: Discussionmentioning
confidence: 78%
“…Three novel fetal echocardiographic measurements of the aortic arch were performed using a sagittal view of the aortic arch in ventricular systole. The left common carotid‐to‐left subclavian artery distance (LCSA) was measured along the outer edge of the distal transverse arch using the distal boundary of the left common carotid artery to the proximal boundary of the left subclavian artery (Figure a), as previously described in postnatal evaluation for CoA . The angle between the AAo and DAo (AAo–DAo angle) was defined as the angle created by two straight lines: One straight line was drawn proximal (above the aortic valve) to distal (just prior to the first head vessel) along the internal boundary of the Aao, and the second line was drawn distal (distal thoracic aorta) to proximal (just prior to the isthmus) along the internal boundary of the DAo (Figure b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates with clinically significant CoA should be hospitalised for continuous administration of prostaglandin E1, to keep the PDA open 22. Patients with subtle clinical and/or diagnostic signs require close clinical and echocardiographic observation to determine whether PDA-closure results in clinically significant CoA 22.…”
Section: Neonatal and Infantile Presentationmentioning
confidence: 99%
“…Patients with subtle clinical and/or diagnostic signs require close clinical and echocardiographic observation to determine whether PDA-closure results in clinically significant CoA 22. Diagnosis of milder cases of CoA is important because hypertension and compensatory LV hypertrophy due to increased LV afterload may occur later in life 6…”
Section: Neonatal and Infantile Presentationmentioning
confidence: 99%